How to Use Deterrents to Stop Damage Caused by Nuisance Wildlife in Your Yard - Holly K. Ober; Arlo Kane (EDIS)
Many of us try to attract particular types of wildlife to our yards so that we can observe them. We often select plants and other materials that we know provide food, cover, and water for those animals we like to watch. However, when unwanted wildlife visits your yard and cause damage, you might need to consider the use of tactics that could deter these unwanted species. This 8-page fact sheet was written by Holly K. Ober and Arlo Kane, and published by the UF Department of Wildlife Ecology and Conservation, October 2012.